Fascismo à brasileira : juventude e imprensa como instrumentos de doutrinação da ação integralista brasileira (1932-1937) - Santorum, Andrelise Gauterio (2018)
For the purpose of mass indoctrination and gaining followers and supporters, the Ação Integralista Brasileira (AIB) engendered a set of control mechanisms. By the analisys of these mechanisms, it is possible to underestand the organic nature of the fascist movement in Brazil. This reaserch aims to investigate youth as one of the specific segments of the fascist movement, based on the periodic press. It seeks to underestand how the organization of the youngsters was used as an indoctrination instrument by AIB, with the objective of founding the Integralist Youth and, at the same time, molding the future followers of the movement. In order to do so, this dissertation presents a qualitative analisys by sampling, revealing how youth instrumentalization was done. The theoretical reference selected to support this analisys was the political culture. This reaserch intends to examine the discourse delivered by the official Integralist written press, in order to expose the mobilization mechanisms, used by the movement to engage young people. The investigation will explore four periodicals of great expression for the movement: the newspapers A Offensiva and Monitor Integralista and the magazines Anauê! and Brasil Feminino. In addition, a series of documents tha marked out important issues about youth in the movement were also examined. Regarding to conceptual aspects, the research proposes a reflection based on the youth sociology: youth is defined beyond age range, but based in symbols and representations, which are redefined throughout history. It provides a broader perspective to comprehend the youth engagement in the fascism lines